The effects of sleep deprivation and text messaging on pedestrian safety in university students. Issue 9 (28th March 2020) - Fobian, Aaron D; Rouse, Jenni; Stager, Lindsay M; Long, Dustin; Schwebel, David C; Avis, Kristin T
Abstract: Study Objectives: This study assesses the impact of sleep deprivation and text messaging on pedestrian injury risk. Methods: A total of 36 university students engaged in a virtual reality pedestrian environment in two conditions: sleep deprived (no sleep previous night) and normal sleep (normal sleep routine). Sleep was assessed using actigraphy and pedestrian behavior via four outcomes: time to initiate crossing, time before contact with oncoming vehicle, hits/close calls, and looks left/right. During each condition, participants made half the crossings while text messaging. Participants also completed the Useful Field of View test, the Psychomotor Vigilance Test, and Conners' Continuous Performance Test in both conditions. Results: While sleep deprived, students crossed significantly closer to oncoming vehicles compared with after normal sleep. While text messaging, crossed closer to vehicles and took longer to initiate crossings. Safety risks were amplified through combined sleep deprivation plus text messaging, leading to more virtual hits and close calls and shorter time before vehicle contact while crossing. Sleep-deprived students demonstrated impairments in functioning on cognitive tests. Conclusions: University students' pedestrian behavior was generally riskier, and their cognitive functioning was impaired, when sleep deprived compared with after normal sleep. This effect was exacerbated when distracted by text messaging.